Archaeometric study of mortars from the Pisa's Cathedral Square (Italy). (October 2018) - Lezzerini, Marco; Raneri, Simona; Pagnotta, Stefano; Columbu, Stefano; Gallello, Gianni
Highlights: Mortars from some buildings in the Miracles Square (Pisa, Italy) were studied. Multi-methodological investigation was applied (OM, XRF, XRPD, TG-DSC and SEM-EDS). Raw materials used in the Miracles Square over the time were identified. New insights on mortar manufacture technology were provided. Abstract: The present work is focused on the study of forty-two mortars used in the construction of both Roman buildings, old Pisa's Cathedral and Modern structures in the Miracles Square (Italy). This area, included since 1987 in the World Heritage List of the UNESCO, is famous for the presence of an important historical complex built in the Middle Ages (the Cathedral, the Baptistery, the Leaning Tower and the Monumental Cemetery). The archaeologists discovered some structures related to more ancient periods: the Roman domus (1st–5th centuries) and the older cathedral with its foundations and crypt (10th century). Based on OM, XRF, XRPD, TG-DSC and SEM-EDS analyses, the main characteristics of binder and aggregate of the mortars have been determined, and some raw materials used for the production of the analysed binding materials have been identified.